2017
DOI: 10.4314/ejhs.v27i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Timing of first antenatal care visit and its associated factors among pregnant women attending public health facilities in Addis Ababa, Ethiopia

Abstract: BACKGROUND: Early initiation of antenatal care visits is an essential component of services to improving maternal and new born health. The Ethiopian Demographic and Health Survey conducted in 2011 indicated that only 11% of pregnant women start antenatal care in the first trimester. However, detailed study to identify factors associated with late initiation of care has not been conducted in Addis Ababa where access to health services is almost universal. The aim of this study was to assess the level of late fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
33
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 18 publications
27
33
5
Order By: Relevance
“…Distance limits the ability and willingness to seek health care where the road network is poor and the common means of transport is by motorcycles. These reasons are similar to a study conducted in Ethiopia where financial constraints where amongst the commonest reasons for late antenatal care booking [9].…”
Section: Perceived Health Systems Barriers To Early Antenatal Caresupporting
confidence: 86%
“…Distance limits the ability and willingness to seek health care where the road network is poor and the common means of transport is by motorcycles. These reasons are similar to a study conducted in Ethiopia where financial constraints where amongst the commonest reasons for late antenatal care booking [9].…”
Section: Perceived Health Systems Barriers To Early Antenatal Caresupporting
confidence: 86%
“…Surprisingly, although women who attained secondary education level were less likely to seek late ANC, it contributed to 80% odds of seeking late ANC attendance. This is in pertinent with the findings of a study which was done in Ethiopia where majority (87%) of the women who sought ANC late had a low of education [17]. Another study done in Uganda [2] also indicated that the level of education played a significant role in seeking ANC services.…”
Section: Association Between Socio-demographics and Late Anc Seeking supporting
confidence: 75%
“…This nding was greater than a study conducted in Colombia (29.7%) [14], which might be attributable to demographic and cultural differences. The nding was less than a study conducted at Debrebirhan health institutions (73.8%) [17], Gonder town (64.9%) [22], and study conducted at Southern Ethiopia (79.8%) [21]. this might be attributable to the difference in the time of the study.…”
Section: Discussionmentioning
confidence: 74%